1997
DOI: 10.1182/blood.v89.6.1931
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Mononuclear Cells Induce Programmed Cell Death in Human Endothelial Cells and May Prevent Repair: Role of Cytokines

Abstract: Human umbilical vein endothelial cells (HUVECs) undergo programmed cell death (apoptosis) after coculture with peripheral blood mononuclear cells (PBMCs) preactivated by ionizing radiation (IR) or by bacterial endotoxin (lipopolysaccharide [LPS]). Cell-to-cell contact-mediated apoptosis could be blocked in both cases by anti–tumor necrosis factor-α (anti–TNF-α) monoclonal antibody MAK195 and also by the antagonistic cytokine interleukin-10 (IL-10). Cell-free PBMC supernatants from both preactivation treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 29 publications
1
27
0
3
Order By: Relevance
“…The prolonged remission of some CD patients after a single infusion of infliximab 18 suggests that infliximab, in addition to neutralizing soluble TNF, might exert more longlasting effects by interacting directly with T cells and/or macrophages via membrane TNF, which is known to be expressed by these cells. 19,20 Indeed, previous studies demonstrated that infliximab induces apoptosis of activated but not resting T cells and also of lamina propria T lymphocytes of patients with active CD. 14,15 Furthermore, Lugering et al 8 reported that infliximab induces apoptosis of peripheral blood monocytes from both healthy controls and patients with chronic active CD.…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged remission of some CD patients after a single infusion of infliximab 18 suggests that infliximab, in addition to neutralizing soluble TNF, might exert more longlasting effects by interacting directly with T cells and/or macrophages via membrane TNF, which is known to be expressed by these cells. 19,20 Indeed, previous studies demonstrated that infliximab induces apoptosis of activated but not resting T cells and also of lamina propria T lymphocytes of patients with active CD. 14,15 Furthermore, Lugering et al 8 reported that infliximab induces apoptosis of peripheral blood monocytes from both healthy controls and patients with chronic active CD.…”
Section: Discussionmentioning
confidence: 99%
“…Nondestructive endothelial cell separations may involve cytoskeletal alterations, 29 as well as increased endothelial permeability. It is well established that cytokines capable of affecting endothelial cells, e.g., interleukins and tumor necrosis factor ␣ may be released by infiltrating macrophages, 30 activated Kupffer cells, 23 or even endothelial cells themselves. 24 Endothelial disruption may involve release of free radicals and induction of oxidative stress mediated by xanthine oxidase activity in Kupffer and endothelial cells as previously documented.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Perfusionreperfusion injury arising from cell embolizations as discussed previously may additionally cause cytokine release, including secondary decline in sinusoidal blood flow, 23 depletion of antioxidant glutathione activity, 33 and finally endothelial disruption. 30 Certainly, in response to hypoxia and other stimuli, parenchymal cells release specific factors, such as VEGF/VPF, hepatocyte growth factor, transforming growth factor ␣, and fibroblast growth factor. 34,35 Under hypoxic conditions, endothelial cells are known to exhibit VEGF/VPF receptor up-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…LPS has been shown to induce endothelial apoptosis in vitro and also, although not in all studies, in vivo [43]. Interaction with other cells may influence endothelial apoptosis; for example, LPS-activated monocytes have been shown to contribute to endothelial apoptosis in vitro [44]. Endothelial apoptosis has been shown to contribute to a procoagulant state in vitro [45].…”
Section: Apoptosis and Circulating Ecs (Cecs)mentioning
confidence: 97%